One-pot synthesis of functionalized germanium nanocrystals from a single source precursor1. Issue 6 (14th February 2015) - Purkait, Tapas K.; Swarnakar, Anindya K.; De Los Reyes, Glenda B.; Hegmann, Frank A.; Rivard, Eric; Veinot, Jonathan G. C.
<x xml:space="preserve">Abstract</x> A general single-pot synthesis of hydrophilic and hydrophobic germanium NCs from single source precursor is reported.